Comparison of Outcomes for Pediatric Trauma at Different Types of Trauma Centers: The Unresolved Mystery. Issue 6 (June 2018) - Elkbuli, Adel; Lopez, Jennifer R.; Villarroel, Paul Perales; Ang, Darwin; Liu, Huazhi; Boneva, Dessy; Morejon, Orlando; Hai, Shaikh; McKenney, Mark
In Florida, injured children can receive emergent care at one of three types of state-approved trauma centers (TCs). A Level 1 combined adult/pediatric TC (L1, A + P), a Level 2 TC with an associated pediatric hospital (L2 + PH) or a pediatric TC at a pediatric hospital (PTH). This study aims to compare the mortality outcomes between Florida L1, A + Ps, to L2 + PHs, and PTHs. A retrospective review of dataset from the Agency for Health Care Administration compared outcomes from 2013 to 2016 at all three types of TCs. Outcomes were stratified by using the observed over expected mortality (O/E). Significance defined as P < 0.05. A total of 13, 428 pediatric trauma patients were treated at all three TCs (L1, A + P, L 2 + PHs, or PTH). L1, A + Ps treated 6975 pediatric patients with 104 deaths [crude mortality rate (CMR) 1.49%, O/E = 0.96], L2 + PHs treated 4066 patients with 69 deaths (CMR 1.70%, O/E = 1.21), PTHs treated 2387 patients with 34 deaths (CMR 1.42%, O/E = 1.25). When O/E's at L1, A + Ps and L2 + PHs were compared, results were statistically significant (P = <0.03), but not at L1, A + P versus PTHs. This is the first study to reveal that Level 1 adult/pediatric TCs have lower mortality rates compared with Level 2 TCs with an associated pediatric hospital. Level 1, A + P TCs had similar outcomes to pediatric TCs at standalone pediatric hospitals.